2016
DOI: 10.1002/biot.201600037
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free live cell imaging by Confocal Raman Microscopy identifies CHO host and producer cell lines

Abstract: As a possible viable and non‐invasive method to identify high producing cells, Confocal Raman Microscopy was shown to be able to differentiate CHO host cell lines and derivative production clones. Cluster analysis of spectra and their derivatives was able to differentiate between different producer cell lines and a host, and also distinguished between an intracellular region of high lipid and protein content that in structure resembles the Endoplasmic Reticulum. This ability to identify the ER may be a major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Based on the average Raman spectra from single cells and multivariate analysis, the authors showed that producing cells could be distinguished from their non-producing host cells, enabling Raman microspectroscopy as a label-free tool to identify protein-producing cells from a heterogeneous cell pool after transfection [1]. The authors identified several Raman bands that differed between the high-producer and non-producer cells.…”
Section: The Authors Declare No Financial or Commercial Conflict Of Imentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the average Raman spectra from single cells and multivariate analysis, the authors showed that producing cells could be distinguished from their non-producing host cells, enabling Raman microspectroscopy as a label-free tool to identify protein-producing cells from a heterogeneous cell pool after transfection [1]. The authors identified several Raman bands that differed between the high-producer and non-producer cells.…”
Section: The Authors Declare No Financial or Commercial Conflict Of Imentioning
confidence: 99%
“…An ideal technological platform for recombinant cell line development would allow for the label-free identification of protein expression levels based on very small cell numbers or even at the single cell level, at an early stage of the cell cloning procedure. As reported by Prats Mateu et al, Raman microspectroscopy is a potential technique that could address these needs [1]. In their study, single cells were scanned using Raman microspectroscopy and two established recombinant CHO cell lines, one producing the monoclonal antibody adalimumab and a second one producing human diamine oxidase, were investigated.…”
mentioning
confidence: 98%
See 3 more Smart Citations